PKM MENEJEMEN MARKETING UMKM - Fajarina, Maskhurin; Nurul Laili, Elisa; Indrawan, Fani; Ertika Daristin, Pipit; Bahroodin, Ariga; Ansori, Sholihul; Anah, Lik; Amer, Afizan (ABIDUMASY, 2024)
Marketing is very important for entrepreneurs to attract consumers so as to increase sales results. Knowledge about branding and marketing is not easy, it is not enough just once or twice, but it needs to be done continuously. Apart from that, marketing is not just about offering to potential consumers, but requires management to maximize marketing results. Therefore, training and assistance to the public regarding marketing management, especially for novice entrepreneurs, is very important. This community service regarding "marketing" is carried out to provide knowledge and assistance regarding "marketing management" to micro economics at Unhasy Jombang Indonesia and UiTM Malaysia and the surrounding communities. The PKM participants consist of micro businesses in Unhasy and its surroundings and UiTM and its surroundings. Using Seminar and Mentoring methods. The result of this PKM is that partners receive continues assistance in carrying out marketing management to improve marketing quality and increase sales results.